PENERAPAN NUMBERED HEAD TOGETHER DENGAN PENDEKATAN GUIDED NOTE TAKING PADA MATERI HIDROKARBON (Universitas Negeri Semarang, 2013)
Submission of hydrocarbon material with the lecture method needs to be supplemented with other methods for improving learning outcomes that are not optimal. This study aimed to investigate the differences of learning outcomes in hydrocarbon materials of high school class X using cooperative learning model Numbered Head Together (NHT) types Guided Note Taking (GNT) aproached with conventional learning models. The population of this research is students class X of an high school in Semarang academic year 2011/2012. Analysis of preliminary data produced learning outcomes and homogeneous normal population. Sampling was done with random sampling techniques, class XA as the experimental class and class XD as the control group. The study was designed in group control of pre test post test. Data was analysing by using the t test. Analysis data showed that in the experimental class N-gain is 0.65 while N-gain control class is 0.56. Average difference test obtained t count (2,28) t table (2,00) means the learning outcomes of experimental class is better than control class. The average results of the learning outcomes of experimental class is 78.60, with completeness classical 85.71%. The average results of the learning outcomes of control class is 73.43, with completeness classical 71.42% so there is a significant difference in learning outcomes hydrocarbon materials in chemistry class X of High School students using cooperative learning models NHT type GNT aproached against students using conventional learning models.